Repeated Long-Term Sub-concussion Impacts Induce Motor Dysfunction in Rats: A Potential Rodent Model - Lavender, Andrew P.; Rawlings, Samuel; Warnock, Andrew; McGonigle, Terry; Hiles-Murison, Bailey; Nesbit, Michael; Lam, Virginie; Hackett, Mark J.; Fitzgerald, Melinda; Takechi, Ryusuke (Frontiers in Neurology, 2020)
Whilst detrimental effects of repeated sub-concussive impacts on neurophysiological and behavioural function are increasingly reported, the underlying mechanisms are largely unknown. Here, we report that repeated sub-concussion with a light weight drop (25g) in wild-type PVG rats for 2 weeks does not induce detectable neuromotor dysfunction assessed by beamwalk and rotarod tests. However, after 12 weeks of repeated sub-concussion, the rats exhibited moderate neuromotor dysfunction. This is the first study to demonstrate development of neuromotor dysfunction following multiple long-term sub-concussive impacts in rats. The outcomes may offer significant opportunity for future studies to understand the mechanisms of sub-concussion-induced neuropsychological changes.